Carboxylation Enhances Fragmentation of Furan upon Resonant Electron Attachment - Zawadzki, Mateusz; Luxford, Thomas F M; Kočišek, Jaroslav (The journal of physical chemistry. A, 2020)
We report a dissociative electron attachment study to 2-furoic acid (C5H4O3) isolated in a gas phase, which is a model molecule consisting of a carboxylic group and a furan ring. Dissociation of furan by low energy electrons is accessible only via electronic excited Feshbach resonances at energies of incident electrons above 5 eV. On the other hand, carboxylic acids are well-known to dissociate via attachment of electrons at subexcitation energies. Here we elucidate how the electron and proton transfer reactions induced by carboxylation influence stability of the furan ring. Overlap of the furan and carboxyl π orbitals results in transformation of the nondissociative π2 resonance of the furan ring to a dissociative resonance. The interpretation of hydrogen transfer reactions is supported by experimental studies of 3-methyl-2-furoic and 5-methyl-2-furoic acids (C6H6O3) and density functional theory (DFT) calculations.